Ruang Lingkup Sasaran Dan Pelaksanaan Bimbingan Dan Konseling Di Sekolah Dan Di Luar Sekolah - Rizkiya Aji; Anggun Mutia; Chika Abelia Navisa; Imas Purnamasari; Titin Sunarti (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Guidance and counseling constitute a professional service with a broad scope of targets and implementation, extending beyond school settings to various contexts outside formal education. This study aims to examine the scope of targets and the implementation of guidance and counseling services both in schools and outside schools through a conceptual and literature-based analysis. In school settings, guidance and counseling services are directed toward students and systematically implemented through personal, social, academic, and career guidance integrated into the educational system. Outside schools, counseling services are carried out in family, community, social, and religious institutions, emphasizing flexible and context-sensitive approaches that respond to diverse individual needs. The findings indicate that effective implementation of guidance and counseling is strongly influenced by the professionalism of counselors, adequate management of services, and collaboration among stakeholders. The integration of school-based and community-based counseling services strengthens the role of guidance and counseling as a lifelong support system that promotes personal development, social adjustment, and psychological well-being. Therefore, comprehensive and adaptive counseling practices are essential to address the complex challenges faced by individuals in various life settings.